HL-A8: a genetic link between dermatitis herpetiformis and gluten-sensitive enteropathy - Stephen I. Katz; Z. Myron Falchuk; Mark V. Dahl; G. Nicholas Rogentine; Warren Strober (The Journal of Clinical Investigation, 1972)
Histocompatibility antigen HL-A8 was found in 58% of 26 patients with dermatitis herpetiformis (DH) compared to 24% of a normal group. This difference in antigen frequency is significant at the P < 0.003 level. In a previous study, the frequency of this same genetic marker was found to be significantly increased in patients with gluten-sensitive enteropathy (GSE) (88% in patients vs. 22% in controls). The finding of an increased incidence of the HL-A8 antigen in both DH and GSE supports the concept that these diseases are related and provides a genetic basis for the association between the two.